2011
DOI: 10.5271/sjweh.3181
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the decision to extend working life or retire

Abstract: Objective The aim of this study was to evaluate factors within nine identified areas that influence why some older workers want to (or believe they can) work until age 65 years or beyond, whereas others leave the workforce earlier. MethodsThe questionnaire-based, cross-sectional study included 1792 respondents aged 55-64 years, employed in the healthcare sector in Sweden. Using logistic regression, we investigated the associations between statements within nine areas and two outcome measures: (i) whether the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
196
2
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(229 citation statements)
references
References 20 publications
23
196
2
8
Order By: Relevance
“…In van Rijn et al's meta-analysis (1), a statistically significant increased risk of early retirement was reported (pooled RR 1.27), while recent studies using a competing risks approach did not find a significant relation (HR 0.91-1.11, SHR 0.87-1.10) (7,8). A possible explanation for these mixed findings is that in this exit route other factors, such as financial arrangements, social situations, and welfare state regime, play a more prominent role (5,44,45). Furthermore, there is some qualitative evidence that both poor and good health can play a role in the transition to early retirement.…”
contrasting
confidence: 39%
“…In van Rijn et al's meta-analysis (1), a statistically significant increased risk of early retirement was reported (pooled RR 1.27), while recent studies using a competing risks approach did not find a significant relation (HR 0.91-1.11, SHR 0.87-1.10) (7,8). A possible explanation for these mixed findings is that in this exit route other factors, such as financial arrangements, social situations, and welfare state regime, play a more prominent role (5,44,45). Furthermore, there is some qualitative evidence that both poor and good health can play a role in the transition to early retirement.…”
contrasting
confidence: 39%
“…Based on our results, early retirement is not driven by health problems. Other factors, like financial arrangements and social factors, might be of greater importance for voluntary routes of exit (5). The discrepancy between studies on the influence of poor health on early retirement might partly be explained by different definitions of early retirement.…”
Section: Discussionmentioning
confidence: 89%
“…From previous research it is known that poor health plays a role in exit from paid employment, particularly due to disability pension (3)(4)(5)(6). Several studies also reported that workers with a poor health are more likely to become unemployed (4,(7)(8)(9)(10)(11) and, to a smaller extent, to retire before the statutory retirement age (4,11,12).…”
mentioning
confidence: 98%
“…In general, these pathways are to a lesser extent driven by health problems (1). Other financial or social factors might play a more important role in these pathways of exit from work than might be the case when leaving the labor market through a specific health-related pathway such as disability pension (43).…”
Section: Acknowledgmentsmentioning
confidence: 99%